Focused radiofrequency treatment of postpartum vaginal relaxation syndrome - Yu. E. Dobrokhotova; T. S.K. Nagieva; E. N. Kareva (Акушерство, гинекология и репродукция, 2020)
Aim: to assess the efficacy and safety of non-ablative radiofrequency treatment in the postpartum period in patients with vaginal relaxation syndrome and other initial manifestations of pelvic floor dysfunction (PFD).Materials and Methods. 44 patients with complaints of the initial manifestations of PFD were enrolled into prospective randomized comparative study: 30 women in the main group and 14 in the control group. Diagnostic methods included medical history collection, objective examination, assessing condition of the perineum by visual inspection; standard clinical and laboratory studies; using the questionnaire for calculating the Female Sexual Function Index (FSFI-19). Staging of pelvic organ prolapse was performed according to the POP-Q classification (Pelvic Organ Prolapse Quantification system). Measurement of the pelvic floor muscle contraction strength was performed by using a perineometer. A course of 3 procedures of radiofrequency non-ablative exposure of the vulvovaginal tissues in patients from the main group was performed 2 months after delivery, with 7-day interval. Assessment of the collagenogenesis and neoangiogenesis was carried out base on measuring expression level of the mRNA specific to proteins of the vaginal connective tissue by using real-time polymerase chain reaction.Results. Our study allowed to find that anatomical and functional state of the vulvovaginal area and perineum were significantly improved as well as relief of PFD symptoms. The level of expression of decorin mRNA in patients from the main group before and after treatment were 0.1 ± 0.035 and 0.047 ± 0.002, respectively (p = 0.02, Wilcoxon t-test). The median values of mRNA expression of matrix metalloproteinase type 2 before and after treatment were 0.0177 and 0.013, respectively (p = 0.03). The expression of type III collagen mRNA before and after treatment was 0.0675 and 0.0109, respectively (p = 0.03).Conclusion. The data obtained by us demonstrate positive effects after using monopolar radiofrequency therapy on the tissues in the vulva, vagina and perineum of patients in the postpartum period. However, clinical improvement in patients with PFD represents a cumulative result of morphological and functional changes in the tissues of the perineum as well as vulvovaginal region. We believe it is irrational to associate such positive effects solely with altered magnitude of the metabolism of collagen and other extracellular matrix proteins, due to dynamic balance and genetic determinism of decay and production of connective tissue proteins. The safety and role of radiofrequency therapeutic procedures in prevention and treatment of PFD require further investigation by assessing new markers and research methods, by extending observation period as well as increasing amount and quality of clinical observations.